Isotope dilution-ultra performance liquid chromatography-tandem mass spectrometry for determination of five alternariol mycotoxins in chestnut - Quanshuai WANG; Weiming SUN (Zhongguo gonggong weisheng)
ObjectiveEstablishment of an isotope dilution-ultra performance liquid chromatography-tandem mass spectrometry (ID-UPLC-MS/MS) method for the simultaneous determination of five alternariol mycotoxins in chestnuts. MethodsThe optimal mass spectrometry conditions for the five target compounds were determined through parameter optimization. The chromatographic peak elution of the target compounds was analyzed, and the optimal chromatographic column and mobile phase were selected. The extraction efficiency of different extraction reagents was compared by recovery experiments to determine the optimal extraction reagent. Finally, the established method was validated. ResultsThe method ultimately used acetonitrile-water-formic acid (70 + 29 + 1) as the extraction reagent for sample pretreatment. A BEH C18 column was used with a mobile phase of acetonitrile -0.15 mmol/L ammonium bicarbonate. The matrix effect of the method could not be ignored, and the internal standard method should be used for quantitative analysis. The limits of detection (LODs) for the five alternariol mycotoxins ranged from 0.10 to 0.50 μg/kg, and the limits of quantitation (LOQs) ranged from 0.30 to 1.50 μg/kg. The recoveries ranged from 80.1% to 111.7%, with relative standard deviations (RSDs) ranging from 2.3% to 8.2%. The correlation coefficients were all ≥ 0.999 0. ConclusionsThis method is simple, rapid, and accurate. The linearity, precision, and recovery meet the methodological requirements, and it is suitable for the simultaneous determination of five alternariol mycotoxins in chestnuts.